Implementation of the Public Housing Savings Act to Meet Community Board Needs - Melia; Rasji (Dinasti Research, 2025)
According to Law of the Republic of Indonesia Number 4 of 2016 concerning Public Housing Savings, it is a long-term fund savings program that is useful in using it for housing financing. So in this writing the author wants to study further regarding the Implementation of the Public Housing Savings Law to Meet the Needs of Community Boards. With normative research methods, the nature of the research is descriptive, using secondary data types using a statutory approach, and analyzed qualitatively. The results and discussion are that this program focuses on increasing access to housing for the community, reducing social disparities, and ensuring that basic needs such as housing are met. By emphasizing the importance of designing policies that not only meet basic needs but also maximize benefits for the entire community. By focusing on better access to housing, efficient fund management, and social welfare, public housing savings are expected to provide broad and sustainable benefits for the Indonesian people, thereby ensuring that the program runs in accordance with applicable legal provisions, which can increase effectiveness and public trust.